Theoretical Study of the trans-3,6-Dimethoxy-1,2,4-trioxane Molecule - Jorge, Nelly (2001)
The molecule of trans-3,6-dimethoxy-1,2,4-trioxane has been studied by the semiempirical molecular orbital AM1 and PM3 methods. The numerical results of the structural study have been analyzed in terms of several stereoelectronic effects and compared with available experimental data. Theoretical predictions derived from both methods are in a good agreement with each other.